1990
DOI: 10.1063/1.104093
|View full text |Cite
|
Sign up to set email alerts
|

Photoconductivity of chemically deposited CdS:Y films

Abstract: Photoconductive CdS:Y films prepared by chemical bath technique show photocurrent to dark current ratios of the order of 105. From scanning electron micrographs, a combination of crystalline and noncrystalline growths are inferred. In the presence of Y a maximum transmission of the order of 60% is found. Traps at depths 0.68 and 0.72 eV are found effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Earlier workers used sophisticated techniques like vacuum evaporation, sputtering, chemical vapour deposition, screen-printing, molecular beam epitaxy, multisource deposition and low pressure hydridetransport chemical vapour deposition etc [1][2][3][4][5][6][7][8][9][10]. In recent years Bhushan and co-workers used chemical deposition technique (dipping technique) and reported quite high photosensitivity [11][12][13][14][15][16], moderate photo voltaic efficiency [17,18], efficient photoluminescence [13,15] and Electroluminescence (EL) [19] in CdS, (Cd-Zn)S & (Cd-Pb)S films. Earlier Nair et al [20] observed many fold improvement in the electro-optical properties of solar assisted chemically deposited CdS type films.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier workers used sophisticated techniques like vacuum evaporation, sputtering, chemical vapour deposition, screen-printing, molecular beam epitaxy, multisource deposition and low pressure hydridetransport chemical vapour deposition etc [1][2][3][4][5][6][7][8][9][10]. In recent years Bhushan and co-workers used chemical deposition technique (dipping technique) and reported quite high photosensitivity [11][12][13][14][15][16], moderate photo voltaic efficiency [17,18], efficient photoluminescence [13,15] and Electroluminescence (EL) [19] in CdS, (Cd-Zn)S & (Cd-Pb)S films. Earlier Nair et al [20] observed many fold improvement in the electro-optical properties of solar assisted chemically deposited CdS type films.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, this technique is very attractive because it is inexpensive, simple and capable of depositing optically smooth, uniform and homogeneous layers. In recent years, Bhushan and co-workers used chemical deposition technique (dipping technique) and reported high photo-sensitivity [9][10][11][12][13][14], moderate photovoltaic efficiency [15,16], efficient photoluminescence (PL) [11,13] and electroluminescence (EL) [17]. In this paper, further results of mixed system (Zn-Cd)S, using chemical deposition technique, are reported and discussed.…”
Section: Introductionmentioning
confidence: 90%
“…A large number of workers [4][5][6][7] also prepared CdS films by such a technique. Many fold improvements were reported by Nair et al [8] due to preparation under solar assisted condition and by Bhushan and co-workers [6,9] in presence of impurities like lanthanides, since alloying can produce base materials of band gaps lying between the band gaps of starting materials and thus can produce materials of higher photo-response and PL emission in desired parts of visible region. With this view (Cd-Pb)S was considered as base material for the present work.…”
Section: Introductionmentioning
confidence: 94%